Characteristics of out-of-hospital cardiac arrest patients in Riyadh province, Saudi Arabia: a cross-sectional study - Almiro, Alyaman; AlQassab, Osamah; Alzeidan, Rasmieh; Binhaddab, Abdulaziz Saad; Alkhorisi, Ahmad M.; Almalki, Hani A; Ghouthalsayd, Muhannad Abdulaziz; Kashour, Tarek; Hersi, Ahmed; Alqarawi, Wael (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Little work has been done on out-of-hospital cardiac arrest (OHCA) in Saudi Arabia. Our goal is to report the characteristics of OHCA patients and predictors of bystander cardiopulmonary resuscitation (CPR). Materials and Methods: This cross-sectional study utilized data from the Saudi Red Crescent Authority (SRCA), a governmental emergency medical service (EMS). A standardized data collection form based on the “Utstein-style” guidelines was developed. Data were retrieved from the electronic patient care reports that SRCA providers fill out for every case. OHCA cases that were attended by SRCA in Riyadh province between June 1st, 2020 and May 31st, 2021 were included. Multivariate regression analysis was performed to assess independent predictors of bystander CPR. Results: A total of 1023 OHCA cases were included. The mean age was 57.2 (± 22.6). 95.7% (979/1023) of cases were adults and 65.2% (667/1023) were males. Home was the most common location of OHCA (784/1011 [77.5%]). The initial recorded rhythm was shockable in 131/742 (17.7%). The EMS mean response time was 15.9 minutes (± 11.1). Bystander CPR was performed in 130/1023 (12.7%) and was more commonly performed in children as compared to adults (12/44 [27.3%] vs 118/979 [12.1%], p=0.003). Independent predictors of bystander CPR were being a child (OR=3.26, 95% CI [1.21 – 8.82], p=0.02) and having OHCA in a healthcare institution (OR=6.35, 95% CI [2.15 – 18.72], p=0.001). Conclusion: Our study reported the characteristics of OHCA cases in Saudi Arabia using EMS data. We observed young age at presentation, low rates of bystander CPR, and long response time. These characteristics are distinctly different from other countries and call for urgent attention to OHCA care in Saudi Arabia. Lastly, being a child and having OHCA in a healthcare institution were found to be independent predictors of bystander CPR.